PAR2 activation on human tubular epithelial cells engages converging signaling pathways to induce an inflammatory and fibrotic milieu - Vesey, David A.; Iyer, Abishek; Owen, Evan; Kamato, Danielle; Johnson, David W.; Gobe, Glenda C.; Fairlie, David P.; Nikolic-Paterson, David J. (Frontiers in Pharmacology, 2024)
Key features of chronic kidney disease (CKD) include tubulointerstitial inflammation and fibrosis. Protease activated receptor-2 (PAR2), a G-protein coupled receptor (GPCR) expressed by the kidney proximal tubular cells, induces potent proinflammatory responses in these cells. The hypothesis tested here was that PAR2 signalling can contribute to both inflammation and fibrosis in the kidney by transactivating known disease associated pathways. Using a primary cell culture model of human kidney tubular epithelial cells (HTEC), PAR2 activation induced a concentration dependent, PAR2 antagonist sensitive, secretion of TNF, CSF2, MMP-9, PAI-1 and CTGF. Transcription factors activated by the PAR2 agonist 2F, including NFκB, AP1 and Smad2, were critical for production of these cytokines. A TGF-β receptor-1 (TGF-βRI) kinase inhibitor, SB431542, and an EGFR kinase inhibitor, AG1478, ameliorated 2F induced secretion of TNF, CSF2, MMP-9, and PAI-1. Whilst an EGFR blocking antibody, cetuximab, blocked PAR2 induced EGFR and ERK phosphorylation, a TGF-βRII blocking antibody failed to influence PAR2 induced secretion of PAI-1. Notably simultaneous activation of TGF-βRII (TGF-β1) and PAR2 (2F) synergistically enhanced secretion of TNF (2.2-fold), CSF2 (4.4-fold), MMP-9 (15-fold), and PAI-1 (2.5-fold). In summary PAR2 activates critical inflammatory and fibrotic signalling pathways in human kidney tubular epithelial cells. Biased antagonists of PAR2 should be explored as a potential therapy for CKD. Word Count: 208